Evaluating electrocoagulation and chemical coagulation for removing dissolved silica from high efficiency reverse osmosis (HERO) concentrate solutions. (April 2017) - Chen, Yingying; Baygents, James C.; Farrell, James
Abstract: High efficiency reverse osmosis (HERO) produces high pH concentrate streams that often contain high levels of dissolved silica. Removal of silica from these concentrate streams is desirable before brine concentration and crystallization. This research investigated removal of dissolved silica from simulated HERO concentrate solutions using electrocoagulation (EC) with mild steel anodes and chemical coagulation with FeCl3 . At pH values of above 10, the mild steel anodes immediately passivated and were not able to deliver Fe 2+ ions into the solution. This necessitated lowering the solution pH value via HCl or FeCl3 addition prior to EC. At pH values ≤10, iron dosing by EC was in agreement with that given by Faraday's law. The optimal initial pH value for operating the EC process was 8, which required addition of 17.8 mM HCl or 5.8 mM FeCl3 . An EC iron dose of 4.0 mM resulted in 76–89% silica removal for solutions with initial pH values between 4 and 8. Higher dosing up to 9.3 mM increased silica removal by only 5%. Chemical coagulation was not as effective as EC, and was able to achieve a maximum removal of 64% with a 4.0 mM FeCl3 dose. Solution ionic strength had no measurable impact on silica removal by EC, but did affect final solution pH values and silica removal by chemical coagulation. For both EC and chemical coagulation, the initial pH value of solution had greater impact on silica removal than the iron dose.